The Impact of Facilities and Means of Transportation on Tourist Satisfaction at Monaco Park Sibiru-Biru Deli Serdang North Sumatra - Gloria Citra Christiany Br Sitepu; Abd. Rasyid Syamsuri; Arief Hadian (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This study aims to analyze the effect of facilities and means of transportation on tourist satisfaction at Monaco Park Sibiru-Biru Deli Serdang, North Sumatra. The research method used in this research is quantitative. The research population is tourists in Monaco Park Biru-Biru, namely 300 visitors from January - March 2022. To determine the sample size of the known population, there are 300 tourists in Monaco Park Biru-Biru. With an error tolerance of 5%, the number of samples that will be used if calculated using the formula is 172 respondents. The results of the study show that facilities have a positive and significant effect on tourist satisfaction in Monaco Park Sibiru-Biru. Means of transportation have a positive and significant effect on tourist satisfaction in Monaco Park Sibiru-Biru. Simultaneously facilities and means of transportation have a positive and significant effect on tourist satisfaction in Monaco Park Sibiru-Biru. R Square (R2) shows the coefficient of determination is 0.719 (71.9%) meaning that the percentage of facilities, transportation facilities, and tourist satisfaction is 71.9% while the remaining is 28.1%.